Effect of accelerated ageing on some surface properties of uv-coated hackberry (Celtis australis l.) wood parquet - Ayata, Ü. (2022)
The importance of UV-curable coatings is currently increasing. In the parquet industry, where UV systems are applied, it is beneficial to investigate new tree species as potential raw materials. This study was carried out to determine the effect of accelerated ageing on some surface properties of hackberry (Celtis australis L.) wood treated with UV system parquet varnish. UV system parquet varnishes were applied to hackberry wood surfaces in three and five layers, according to the requirements of industrial applications. The varnished surfaces were then exposed to UV rays for 252 and 504 h using UVA-340 lamps in a QUV ageing device. Glossiness, colour parameters, pendulum hardness and adhesion strength (pull-off) (MPa) were determined for the coated samples before and after ageing, and the results for the aged and unaged test samples were compared. Analysis of variance showed that the results were significant for all tests. The results for all tests varied by ageing time.